Self-Esteem and Coping Strategies as Correlates of Resilience among Emerging Adults in Bandung - Ahmad Baihaqi; Rifqi Farisan Akbar; Prinska Damara Sastri (International Journal of Marketing & Human Resource Research, 2026)
This research investigated the relationships among self-esteem, coping strategies, and resilience among emerging adults living in Bandung. The study used a quantitative correlational design and involved 150 participants aged 19-29 recruited through purposive, nonprobability sampling. Participants completed measures of self-esteem, coping strategies, and resilience. The analyses included descriptive statistics, gender comparisons, Pearson correlations, tests of regression assumptions, and multiple linear regression. The results showed a positive and statistically significant association between self-esteem and resilience. By contrast, coping strategies were not significantly associated with resilience, either in the bivariate analysis or after self-esteem was entered into the regression model. Although the model as a whole reached statistical significance, it explained only a limited proportion of the variance in resilience. Self-esteem, therefore, emerged as the more salient correlate in this sample. The findings also suggest that resilience may be associated with personal, interpersonal, and contextual resources beyond those examined in this study. Interventions for emerging adults may consequently benefit from promoting constructive self-evaluation while considering the effectiveness and situational suitability of coping responses, rather than their frequency alone